Ministries in the Church in India - S N Arulnesan (Journal of Dharma, 1977)
Ministries in the Church in India is ?, collection of study papers and recommendations based on the findings of a team of eminent Research Scholars who for a whole year dedicated themselves, individually and collectively, to the task of exploring the varieties of ministries that could transform the world in general, and India in particular. It is, as the Editor says, "an offering made to the whole Church in India—in humble and loving homage"— in the confident hope that it will stimulate further study, and enrich pastoral effectiveness in the church.